2009
DOI: 10.3176/eco.2009.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the bank voleMyodes glareolusin the non-vegetative period in NE Lithuania

Abstract: Bank voles (Myodes glareolus) were trapped in north-east Lithuania from October to April in 2004-2008. Investigation of 536 individuals showed that winter growth depression for the species was not strongly expressed, except for the body weight of juveniles in December and January. Only a few skull characters showed stunted growth. The wintering juvenile bank voles attained an average body mass of 14.8 ± 0.07 g and an average body length of 84.3 ± 0.32 mm, while the respective parameters in subadult individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…We found that in M. glareolus growth regression and renewal occurred earlier than in M. arvalis. Growth depression in M. glareolus lasted in December and January and renewal occurred in February (Balčiauskienė et al 2009). Subadults of these voles keep their body mass relatively stable (body mass in April was almost the same as in October), increasing in length for about 8 mm.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We found that in M. glareolus growth regression and renewal occurred earlier than in M. arvalis. Growth depression in M. glareolus lasted in December and January and renewal occurred in February (Balčiauskienė et al 2009). Subadults of these voles keep their body mass relatively stable (body mass in April was almost the same as in October), increasing in length for about 8 mm.…”
Section: Discussionmentioning
confidence: 96%
“…Growth dynamics of X 2 -length of mandibula, excluding incisors, and X 7 -length of mandibular tooth row in subadult M. arvalis in2004-2009.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature might not only affect the stability of the virus, but also the host itself. Bank vole growth may be sensitive to mild winter conditions if they have a negative impact on habitat of the rodents [ 84 ]. In another study, snowfall in December and in April was associated with high host population densities [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Body condition and its seasonal changes were compared to published data, recalculated if required [15,18,[42][43][44].…”
Section: Small Mammal Trapping and Evaluationmentioning
confidence: 99%